Self-diffusion, velocity cross-correlation, distinct diffusion and resistance coefficients of the ionic liquid [BMIM][Tf2N] at high pressure. Issue 37 (27th August 2015) - Harris, Kenneth R.; Kanakubo, Mitsuhiro
Abstract : Distinct diffusion coefficients for 1-alkyl-3-imidazolium [Tf2 N] salts show very similar viscosity dependence; thermodynamic scaling parameters for the reduced transport properties are equal. Abstract : Ion self-diffusion coefficients ( D S i ) have been measured for the ionic liquid 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)amide [BMIM][Tf2 N] at pressures to 200 MPa between 25 and 75 °C and at 0.1 MPa between 10 and 90 °C. Self-diffusion coefficients are reported for 1-ethyl-, 1-hexyl- and 1-octyl-3-methylimidazolium bis(trifluoromethanesulfonyl)amide salts at 0.1 MPa, supplemented by viscosity, electrical conductivity and density measurements. Velocity cross-correlation (VCC, f ij ) and distinct diffusion coefficients ( D d ij ) are calculated from the data. Both D S i and D d ij are analysed in terms of (fractional) Stokes–Einstein–Sutherland (SES) equations. SES and Walden plots show almost identical slopes, with high-pressure isotherms and the atmospheric pressure isobar falling on common, single lines for each property for [BMIM][Tf2 N]. SES plots for the anion self-diffusion coefficients for the [RMIM][Tf2 N] (R = alkyl) series are coincident, whereas those for the cations depend on their alkyl substitution, as do the Walden plots. In common with other [Tf2 N] − salts, the VCC follow the order f −− < f ++ < f +− . The Nernst–Einstein deviation parameter Δ for [BMIM][Tf2 N] is independent of temperature and pressure. Those for the other [Tf2 N] − salts are independent of temperature. Δ increases in magnitude with increasing alkyl chain length on the cation. The transport properties of [BMIM][Tf2 N] are re-examined in terms of density scaling using reduced conductivities and reduced molar conductivities for the first time. Identical scaling parameters ( γ ) are obtained for the several reduced transport properties. This result is supported by data for other ionic liquids. It is suggested that the γ for ionic liquids may depend on packing fraction.